Growth of the (001) face of borax crystals - Suharso Suharso (Universitas Gadjah Mada, 2005)
The growth rates of borax crystals from aqueous solutions in the (001) direction at various relative supersaturations were measured using in situ cell optical microscopy method. The result shows that the growth mechanism of the (001) face of borax crystal at temperature of 20 °C is spiral growth mechanism.